Multidrug-resistant non-typhoidal Salmonella of public health significance recovered from migratory birds in Bangladesh - Card, Roderick M.; Chisnall, Thomas; Begum, Ruhena; Sarker, Md Samun; Hossain, Muhammad Sazzad; Sagor, Md Shahjalal; Mahmud, Mohammad Asheak; Uddin, A. S. M. Ashab; Karim, Md Rezaul; Lindahl, Johanna F.; Samad, Mohammed Abdus (Frontiers in Microbiology, 2023)
Non-typhoidal Salmonella provides an exemplar for the One Health approach as it encompasses public and animal health, food safety, and environmental considerations. The contribution of environmental aspects is currently less well defined. The purpose of this study was to determine the carriage occurrence of non-typhoidal Salmonella in migratory birds in Bangladesh and assess the potential significance to public and animal health. Cloacal swabs (N=453) were collected in years 2018-2020 from Tanguar and Hakaluki Haors, important wetland ecosystems in North-eastern Bangladesh. The prevalence of Salmonella was 13.5% (61 positive swabs). Classical serotyping identified six serovars: Salmonella enterica subsp enterica serovars Perth, Kentucky, Albany, Infantis, Weltevreden, and Brancaster. Resistance towards 14 antimicrobials was assessed by broth microdilution minimum inhibitory concentration determination and the antimicrobial resistance (AMR) genotype established by whole genome sequencing. S. Perth and S. Weltevreden isolates were susceptible and harboured no acquired AMR genes. Isolates from the remaining serovars were multidrug resistant, commonly possessing resistance to tetracycline, ampicillin, chloramphenicol, sulfamethoxazole, trimethoprim, and ciprofloxacin. Salmonella resistant to ciprofloxacin meet WHO criteria for priority pathogens. There was excellent concordance between resistance phenotype and the presence of corresponding AMR genes, many of which reside on Salmonella Genomic Islands. High-level ciprofloxacin resistance correlated with the presence of mutations in the chromosomal gyrB and/or parC genes. The S. Kentucky isolates were ST198, a widely distributed multidrug-resistant lineage reported in humans and animals, and constituting an ongoing risk to public health worldwide. We have demonstrated that multidrug resistant non-typhoidal Salmonella of public health significance can be recovered from migratory birds. A potential for risk can manifest through direct interaction, transmission to food-producing livestock on farms, and dissemination via the long range migratory movements of birds. Risks can be mitigated by measures including continued surveillance and implementation of good farm biosecurity practices.